Effects of Canola Oil on Fatty Acids and Biochemical Traits of Blood Plasma in Broiler Chickens - Al-Tawash , Ali Sami Amin; Al-Bachry, Waleed Sami J.; Al-Khaikani, Salwan Abdel Muaen (International Journal of Poultry Science, 2019)
Objective: Field trials were conducted to investigate the effects of canola oil on broiler chickens in terms of their fatty acid composition and biochemical traits, such as the concentrations of cholesterol, glucose and uric acid. Materials and Methods: The study was conducted using 120 individual Ross 308 broilers at the age of 21 days. The animals were randomly distributed into four equal groups. Canola oil was added to the diets at different concentrations of 0, 3 and 5%, which correspond to treatments T1, T2 and T3, respectively. The fatty acid composition and biochemical characteristics were tested. Results: Saturated fatty acids and blood glucose concentration decreased as the concentration of canola oil increased. There was also a significant increase in cholesterol and uric acid in the treatment groups in comparison to the control group as the concentration of canola oil increased. Conclusion: Canola oil administration decreases the concentrations of saturated fatty acids and blood glucose in broilers, especially at higher levels. However, more studies are needed to detect the mechanism involved.